Outcomes of three different models for sex education and citizenship programs concerning knowledge, attitudes, and behavior of Brazilian adolescents - Campos Márcia; Faúndes Anibal; Sousa Maria Helena de; Cabral Francisco; Silva Ricardo de Castro e; Díaz Margarita; Mello Maeve Brito de (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2005)
Three different school-based sex education and citizenship programs in public schools in Rio de Janeiro, Belo Horizonte, and Salvador, Brazil, were evaluated in a cross-sectional study comparing knowledge, attitudes, and practices in sexuality, citizenship, and gender issues among adolescents participating in the programs' activities as compared to adolescents enrolled in schools without such programs (controls). Results showed that Salvador's program achieved good results, with significant changes in knowledge on sexuality and reproductive physiology, attitudes regarding citizenship, and current use of modern contraceptives; Rio de Janeiro's program succeeded in improving students' knowledge of reproductive physiology and attitudes towards sexuality; Belo Horizonte's participants showed greater knowledge of reproductive physiology and STI/HIV prevention but had less positive attitudes towards gender issues, while reporting greater sexual activity. The main difference between Salvador's program and the others was the focus on creative and cultural activities; Belo Horizonte's main difference was its lack of interaction with health services and professionals. However, after the evaluation Belo Horizonte reframed its educational strategies and launched a scaling-up process in a joint effort with the health and school systems.